Diagnostic test of endometrial cytobrush in cases of perimenopausal and postmenopausal hemorrhage (Medical Journal of Indonesia, 2005)
Perimenopausal menopausal hemorrhage can be due to by a variety of causative factors. One of its dangerous causes is atypical hyperplasia and endometrial carcinoma. There are a number of risk factors for the occurrence of endometrial carcinoma. The group that has this risk belongs to high-risk group. In this high-risk group, it is necessary to have a method to identify the changes in endometrial abnormality. One of the alternatives is the examination of endometrial cytology. The objective of this study was to evaluate the sensitivity, specificity and correlation test between endometrial cytology and endometrial histology. This study was a diagnostic test of cytological examination of the endometrium as compared with endometrial histology. Endometrial cytology was performed with a modification of cytubrush and IUD shell. Specimen was dissolved into the centrifuged NaCl, and its deposits were then processed for cytological examination with Papanicolaou and Giemsa staining. After the taking of cytology, the process was continued with curettage of the endometrium, and the specimens were processed for cytological examination. Both of them were examined by anatomic pathologist. Statistical analysis used diagnostic test using histological examination of curetage specimens as gold standard. During the period of study 45 study samples were collected, among which 12 (26.66%) were endometrial adenocarcinoma, 6 (13.33%) with atypical hyperplasia, 11 (24.44%) with non-atypical hyperplasia, 15 (33.33%) were samples without abnormality, and one sample with endometritis. Actual correlation value was 57.8%, correlation because of possibility 3.38%, and correlation not because of possibility 54.42%, potential correlation not because of possibility 96.62%, and Kappa value 0.56. It was concluded that cytological examination of the endometriurn with cytobrush could be employed as a screening method in the abnormalities of endometrial thickness, with sensitivity of 62.5% and specificity of 62.2%. (Med J Indones 2005; 14: 87-91)Keywords: Endometrial cencer, endometrial cytology